Porous Tantalum Femoral Metaphyseal Cones for Large Femoral Bone Defects in Revision Total Knee Arthroplasty - Nikolaus, O. Brant (JBJS Essent Surg Tech, 2017)
INTRODUCTION: The use of porous tantalum metaphyseal cones provides reliable metaphyseal support and fixation to help restore the joint line in difficult revision total knee arthroplasties (TKAs) in patients with large femoral bone defects. INDICATIONS & CONTRAINDICATIONS: STEP 1: PREOPERATIVE PLANNING: Adequate preoperative radiographs are important to determine the approximate size of the femoral bone defect prior to surgery. STEP 2: INCISION AND EXPOSURE: Adequate exposure during revision knee surgery is key for the safe removal of implants and to minimize bone loss. STEP 3: COMPONENT REMOVAL: It is essential to disrupt the prosthesis-cement interface before attempting to extract well-fixed components. STEP 4: ESTABLISHING A TIBIAL PLATFORM: The first step in revision knee reconstruction is to establish a stable tibial platform. STEP 5: RECONSTRUCTION OF THE FEMUR: Restoring the joint line and posterior condylar offset are the goals of femoral reconstruction. STEP 6: INTRAOPERATIVE ASSESSMENT OF FEMORAL BONE LOSS: Thoroughly assess the quality, quantity, and location of the remaining cancellous and cortical bone to determine the proper technique for reconstruction. STEP 7: SELECTING THE APPROPRIATE METAPHYSEAL CONE AND SHAPING THE FEMORAL METADIAPHYSIS FOR THE FEMORAL CONE: There are different sizes and shapes of metaphyseal cones that can be used when addressing large femoral bone defects. STEP 8: IMPLANTING THE ACTUAL POROUS METAPHYSEAL CONE: During the final impaction of the femoral metaphyseal cone, take care to not cause a fracture. STEP 9: FINAL TRIAL AND CEMENTING OF THE FINAL STEMMED FEMORAL COMPONENT: Place the final stemmed femoral component through the metaphyseal cone and cement it into place. STEP 10: POSTOPERATIVE PROTOCOL: If a stable construct was achieved, the patient may bear weight as tolerated with no specific restrictions on range of motion. RESULTS: We recently performed a retrospective review of the midterm outcomes at mean of 5 years (range, 2 to 10 years) after 159 consecutive revision TKAs with a porous metal femoral metaphyseal cone in 157 patients with large bone defects(4). PITFALLS & CHALLENGES: